Revitalization of Rural Areas of the Carpathian Region in the Context of EU Macro–Regional Strategy - Sytnyk, N.; Humeniuk, V.; Sych, O.; Hlevatska, N.; Глевацька, Н. М. (Babes-Bolyai University, 2022)
Rural areas of the Ukrainian part of the Carpathian Euroregion face several challenges in their development such as declining natural growth, migration, unemployment, low level of gross domestic product per capita, small rural households, having low quality land used for cultivation of a limited number of crops. The introduction of the state strategy for the region could be the instrument to revitalize the rural areas. However, there are unresolved scientific debates about the most effective tools for the strategy that would focus on specific challenges of the mountain rural areas. The aim of the article is to answer the questions: what are the dynamics of the main socio-economic indicators of the mountain rural territories in comparison with the Ukraine and EU? What are the main disadvantages of the region and how they could be solved using the EU experience? The calculation of statistical indicators showed a divergence - differences with the average indicators across the country and the EU in 2011-2019. The method of SWOT analysis reveals the factors of internal and external environment that have a positive and negative impact on the development of rural areas. Based on the European experience of implementation of the Common Agricultural Policy, new elements were proposed to be considered in the Ukrainian strategy: introduction of a systematic approach to the creation of the rural strategy, greening agricultural production and the implementation of the concept of smart villages in Carpathian region. The inclusion of these elements could improve the investment climate in rural areas, which is one of the priorities of rural development of the Ukrainian Carpathian Region.
Ревіталізація сільських територій Карпатського регіону в контексті макрорегіональної стратегії ЄС
Keywords: rural areas; Carpathian; Ukrainian; product; development; strategy; region